Analisis Kelayakan Pendirian Proyek Stasiun Radio Guna Mengetahui Profit Maksimum - Cukup Santoso (Jurnal Teknik Industri, 2008)
Elegibility study is research about could or not a invest project can do well and can give profit level which is suitable or can be use economically. To determine how competend or not the building a project that is seen from some of aspects which support the project building and this project can be success. The research object here was PT. Radio Mitra Suara Batu place in Wukir Number 4 Batu City. This company was active in information service which wish to conduct extention of business by building a new station with different format than other radio station there ever made by this company. Therefore, before company built a new radio station it must do some elegibility study first. In order to not have come too par unintentionally big investing capital for the project which due not profit. Aspect to be studied for example: First, market aspect which determine market segmentation and market plan. Second, technical and production aspect which determine project location, production capacity, needed facility, kind of technology that is use and project layout. Third, management aspect which determine organitation structure, job description, employee needed and work scheduling. Fourth, finance aspect which determine total invest, remains value, decrease value, earnings projection, incoming ang outgoing cash stream and Rate of Return value as standart of project elegibility. Fifth, industrial environmental aspect which determine which supplier one to be chose and how emulation industrially is similar. Sixth, economic, social and political aspect will be known impact from project building and way to overcome. Seventh, aspect of law will support legality of building of project from facet punish. To maximize earning using Linier Programming method. Sum up earnings with Linier Programming method is Rp6,222,420.00/day and Rp186,672,600.00/month and this value there are difference Rp2,400,00/month that is smaller than manual calculation.